Differences and similarities between ecological and economic models for biodiversity conservation - Martin Drechsler; Volker Grimma; Jaroslav Myšiak; Frank Wätzold (UFZ-Umweltforschungszentrum Leipzig-Halle, 2005)
In this paper we investigate an important obstacle which substantially complicates cooperation between ecologists and economists but which has received little attention so far: differences between the modelling approaches in economics and ecology. To understand these differences, 60 models addressing issues relevant to biodiversity conservation have been selected randomly from eight international economic and ecological journals. The models have been compared according to a number of criteria including the level of generality/universality the models aim at; the mathematical technique employed for formulation and solution of the model; the level of complexity and the way time, space and uncertainty are taken into account. The economic models sampled are formulated and analysed analytically, tend to be relatively simple and are generally used to investigate general questions. Furthermore, they often ignore space, dynamics and uncertainty. Although some ecological models have similar properties, there is also a substantial number of another type of ecological models that are relatively complex and analysed by simulation. These models tend to be rather specific and often explicitly consider dynamics, space and uncertainty. The integrated ecological-economic models are observed to lie 'in the middle' between ecological and economic models, an unexpected result being that they are not more complex than ecological and economic models (as one could have expected from a simple 'merger' of both modelling attitudes), but have an intermediate complexity.
Keywords: B40; C60; Q57; 330; Ecological-economic modelling; modelling; biodiversity; conservation